2014
DOI: 10.1155/2014/327801
|View full text |Cite
|
Sign up to set email alerts
|

Disease Management of Early Childhood Caries: ECC Collaborative Project

Abstract: Until recently, the standard of care for early childhood caries (ECC) has been primarily surgical and restorative treatment with little emphasis on preventing and managing the disease itself. It is now recognized that surgical treatment alone does not address the underlying etiology of the disease. Despite costly surgeries and reparative treatment, the onset and progression of caries are likely to continue. A successful rebalance of risk and protective factors may prevent, slow down, or even arrest dental cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In addition to the scientific evidence that supports the different interventions proposed in this paper, additional evidence indicates that remineralization of caries lesions can take place in enamel and dentin [ 82 ]. An early childhood caries management approach that focuses on home care, prevention, and restorative care resulted in positive outcomes [ 83 ]. Sealants and resin infiltration have shown potential of slowing the progression or reversing non-cavitated caries lesions [ 84 - 86 ].…”
Section: Implementation Of Iccms™mentioning
confidence: 99%
“…In addition to the scientific evidence that supports the different interventions proposed in this paper, additional evidence indicates that remineralization of caries lesions can take place in enamel and dentin [ 82 ]. An early childhood caries management approach that focuses on home care, prevention, and restorative care resulted in positive outcomes [ 83 ]. Sealants and resin infiltration have shown potential of slowing the progression or reversing non-cavitated caries lesions [ 84 - 86 ].…”
Section: Implementation Of Iccms™mentioning
confidence: 99%
“…Caries can progress rapidly if left untreated, resulting in pain and infection; thus, early diagnosis and prevention is of great importance. 1 , 2 , 3 , 4 , 5 Salivary analyses have been used to help assess the risk of caries by measuring the saliva's buffering capacity and bacterial content. 6 Recent studies have also indicated that a comprehensive compositional analysis of the complexity of oral fluid is very important in the assessment of the severity of caries.…”
Section: Introductionmentioning
confidence: 99%
“…Dental personnel may also serve effectively as helping professionals in ECC counseling 4748 but would require sufficient compensation to routinely implement disease management protocols in practice 49 to offset income lost from reductions in dental repair. The high cost of dental professionals and their sophisticated clinical expertise, however, suggest that engaging them in family-level counseling is inherently inefficient while limiting their availability to function at the top of their scope of practice.…”
Section: Evidentiary Consideration Of Non-conventional Health Workersmentioning
confidence: 99%